2021
DOI: 10.3389/fvets.2021.695553
|View full text |Cite
|
Sign up to set email alerts
|

High Co-infection Status of Novel Porcine Parvovirus 7 With Porcine Circovirus 3 in Sows That Experienced Reproductive Failure

Abstract: Porcine parvoviruses (PPVs) and porcine circoviruses (PCVs) infect pigs worldwide, with PPV1–7 and PCV2 infections common in pigs. Although PPV7 was only identified in 2016, co-infection of PPV7 and PCV2 is already common, and PPV7 may stimulate PCV2 replication. PCV3, a novel type of circovirus, is prevalent in pig populations worldwide and considered to cause reproductive disorders and dermatitis nephrotic syndrome. In recent studies, pigs were commonly infected with both PCV3 and PPV7. Our objective was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…For example, pigs coinfected with PCV2 and porcine parvovirus (PPV) became dull, developed jaundice and hepatomegaly, and some even died [ 32 ]. Coinfection of PCV2 or PCV3 with PPV leads to severe viremia and reproductive disorders [ 33 , 34 , 35 ]. In addition, PCV-2 infection inhibits the response of immune-related signaling pathways and promotes the replication of viruses such as pseudorabies virus and porcine reproductive and respiratory syndrome virus [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, pigs coinfected with PCV2 and porcine parvovirus (PPV) became dull, developed jaundice and hepatomegaly, and some even died [ 32 ]. Coinfection of PCV2 or PCV3 with PPV leads to severe viremia and reproductive disorders [ 33 , 34 , 35 ]. In addition, PCV-2 infection inhibits the response of immune-related signaling pathways and promotes the replication of viruses such as pseudorabies virus and porcine reproductive and respiratory syndrome virus [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, co-infections of PCV3 with other pathogens may also lead to reproductive failure or even increase the severity of the disease [80,82,84]. As reported by Dal Santo et al, 93.1% of 270 PCV3-positive mummified fetuses were co-infected with PPV, PCV2, and/or Leptospira spp.…”
Section: Reproductive Disordersmentioning
confidence: 93%
“…[80]. Mai et al also found that the positive rates of PPV7 in PCV3-positive reproductive failure-serum and PCV3-positive aborted fetus samples were significantly higher than that of the PCV3-positive non-reproductive failure serum samples [84]. Meanwhile, the positive rates of PCV3 in PPV7-positive samples were obviously higher than that of the PPV7-negative samples [84].…”
Section: Reproductive Disordersmentioning
confidence: 96%
“…The prevalence of PPV7 in China has been examined by different researchers, and the prevalence varies. It is 32.8% (21/64) in Guangdong ( 12 ), 27.3% (105/385) in Guangxi ( 16 ), 20% (24/120) to 74% (148/200) in Anhui ( 17 , 19 , 25 ), 23% (48/209) in Hunan ( 18 ) and 15.4% (67/435) for samples collected in Xinjiang, Hebei, Shandong, Henan, Jiangsu, Anhui, Fujian and Guangdong ( 20 ). However, information concerning the prevalence and genetic evolution of PPV7 is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been reported that the PPV7 positive rate in PCV3 positive serum was significantly higher than that in PCV3 negative serum. Furthermore, the copy number of PCV3 in PPV7 positive samples was significantly higher than that in PPV7 negative serum samples, indicating that PPV7 may be a co-acting factor for PCV3 replication ( 18 ). High coinfection rates of PPV7 and PCV2, or PPV7 and PCV3 were also observed in our study.…”
Section: Discussionmentioning
confidence: 99%